Quiet eye training facilitates competitive putting performance in elite golfers - Vine, S. J.; Moore, L. J.; Wilson, M. R. (Frontiers in Psychology, 2011)
The aim of this study was to examine the effectiveness of a brief quiet eye (QE) training intervention aimed at optimizing visuomotor control and putting performance of elite golfers under pressure, and in real competition. Twenty-two elite golfers (mean handicap 2.7) recorded putting statistics over 10 rounds of competitive golf before attending training individually. Having been randomly assigned to either a QE training or Control group, participants were fitted with an Applied Science Laboratories Mobile Eye tracker and performed 20 baseline (pre-test) putts from 10 ft. Training consisted of video feedback of their gaze behavior while they completed 20 putts; however the QE-trained group received additional instructions related to maintaining a longer QE period. Participants then recorded their putting statistics over a further 10 competitive rounds and re-visited the laboratory for retention and pressure tests of their visuomotor control and putting performance. Overall, the results were supportive of the efficacy of the QE training intervention. QE duration predicted 43% of the variance in putting performance, underlying its critical role in the visuomotor control of putting. The QE-trained group maintained their optimal QE under pressure conditions, whereas the Control group experienced reductions in QE when anxious, with subsequent effects on performance. Although their performance was similar in the pre-test, the QE-trained group holed more putts and left the ball closer to the hole on missed putts than their Control group counterparts in the pressure test. Importantly, these advantages transferred to the golf course, where QE-trained golfers made 1.9 fewer putts per round, compared to pre-training, whereas the Control group showed no change in their putting statistics. These results reveal that QE training, incorporated into a pre-shot routine, is an effective intervention to help golfers maintain control when anxious.